(3TQM GddeY aj GdMSGHs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s; (3TgGH GdOjf CMeO Hf eMeO Hf YeGO GdOjf Hf Ydj GdefUhQj GdSdej, GHf GdgGFe,J (B815 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd eMeO Hf eMeO Hf CMeO Hf eMeO SHW GdeGQOjfi gPG JYdjb eNJUQ LYdJg JhVjMkG Ydi GdebOeI GdeSeGg HGddeY ai Yde GdMSGH s
(3BNQgG (B:s
(3hgh GdLhGH hgPG Sgd hai gPG caGjI def habg Gddg JYGdi hHGddg GdeSJYGf hef CQGO GdRjGOI Ydi Pdc aYdjg HGdhSjdI ddeUfa hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B226s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1562s
Keywords: (3GdQjGVjGJs